2022
DOI: 10.3389/fendo.2022.1039786
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study identified bile acids as potential biomarkers for gastric cancer: A case control study

Abstract: Gastric cancer (GC) is a common lethal malignancy worldwide. Gastroscopy is an effective screening technique for decreasing mortality. However, there are still limited useful non-invasive markers for early detection of GC. Bile acids are important molecules for the modulation of energy metabolism. With an in-depth targeted method for accurate quantitation of 80 bile acids (BAs), we aimed to find potential biomarkers for the early screening of GC. A cohort with 280 participants was enrolled, including 113 GC, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Li et al designed a case–control study in a Chinese population and found that the serum total BA >10 μmol/L can be a diagnostic threshold for the risk of gastrointestinal cancer, especially for the risk of esophageal cancer and GC (Li et al, 2022b ). The latest clinical research (Pan et al, 2022 ) presented clearly promoted conjugated and unconjugated BAs in the sera of patients with GC, again showing that serum BAs participate in the development of gastric carcinogenesis apart from GIM. The present transcriptome of the gastric mucosa showed that the overexpression levels of GIM-related genes were consistent with those in the previous reports, such as Cdx2, Nr1h4 , and Cdh17 .…”
Section: Discussionmentioning
confidence: 92%
“…Li et al designed a case–control study in a Chinese population and found that the serum total BA >10 μmol/L can be a diagnostic threshold for the risk of gastrointestinal cancer, especially for the risk of esophageal cancer and GC (Li et al, 2022b ). The latest clinical research (Pan et al, 2022 ) presented clearly promoted conjugated and unconjugated BAs in the sera of patients with GC, again showing that serum BAs participate in the development of gastric carcinogenesis apart from GIM. The present transcriptome of the gastric mucosa showed that the overexpression levels of GIM-related genes were consistent with those in the previous reports, such as Cdx2, Nr1h4 , and Cdh17 .…”
Section: Discussionmentioning
confidence: 92%
“…In targeted Tregs reprogramming, multi-omics approaches combined with novel computational tools can be applied to target various signals and molecules on Tregs ( 243 245 ). It enables a better understanding of the gene regulatory networks regulating Treg function, as well as the identification of additional biomarkers that define Tregs function in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, bile reflux has been shown to be an independent risk factor for precancerous gastric lesions and GC (Zhang et al 2021 ). Especially, HCA a primary bile acid and HDCA, a secondary bile acid, play a crucial role in regulating energy expenditure and were both identified to be decreased in patients with UGC (Pan et al 2022 ). However, our results are inconsistent with previous literature as multiple authors described primary bile acids to be reduced and secondary bile acids to be increased in patients with UGC (Rezen et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%